Electron-Phonon Interaction in the High-𝑇𝐶 Cuprates in the Framework of the Van Hove Scenario - Jacqueline Bouvier; Julien Bok (Advances in Condensed Matter Physics)
Electron-lattice interaction was the original idea of Müller and Berdnorz who chose copper oxides, because of the strong Jahn-Teller effect of the Cu ion leading to the formation of bipolarons. Later several experimental features led to theoretical models based on strong electronic correlations. The high-𝑇𝐶 superconductors cuprates are quasi-bidimensional (2D) and thus lead to the existence of Van Hove singularities (VHs) in the band structure, that is, a peak in the electronic density of states. The presence of VHs near the Fermi-level in the cuprates is now well established. In this context we show that many physical properties of these materials can be explained using electron-phonon interaction, in particular the high critical temperature 𝑇𝐶, the anomalous isotope effect, the superconducting gap and its anisotropy, and the marginal Fermi-liquid properties. These compounds present a topological transition for a critical hole doping 𝑝≈0.21 hole per CuO2 plane.